Safety and efficacy of Lactobacillus parafarraginis DSM 32962 as a silage additive for all animal species. (21st July 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed was asked to deliver a scientific opinion on the safety and efficacy of Lactobacillus parafarraginis DSM 32962 when used as a technological additive intended to improve the production of silage at a proposed application rate of 1 × 10 8 colony forming units (CFU)/kg fresh material. The bacterial species L. parafarraginis is considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. As the identity of the strain has been clearly established and no acquired antimicrobial resistance determinants of concern were detected, the use of the strain as a silage additive is considered safe for livestock species, for consumers of products from animals fed the treated silage and for the environment. The additive is not an eye or dermal irritant but should be considered a potential respiratory sensitiser. No conclusions can be drawn on the skin sensitisation potential of the additive. Three studies with laboratory‐scale silos were made using samples of easy and moderately difficult to ensile forage. In each case, replicate silos containing untreated forage were compared with identical silos containing the same forage to which Lactobacillus parafarraginis DSM 32962 was added to reach an intended concentration of 1 × 10 8 CFU/kg fresh matter. The results showed that the addition of the additive improves significantly the aerobic stability of the silage tested.